A Stretchable and Transparent Electrode Based on PEGylated Silk Fibroin for In Vivo Dual‐Modal Neural‐Vascular Activity Probing. Issue 34 (18th July 2021) - Cui, Yajing; Zhang, Fan; Chen, Geng; Yao, Lin; Zhang, Nan; Liu, Zhiyuan; Li, Qingsong; Zhang, Feilong; Cui, Zequn; Zhang, Keqin; Li, Peng; Cheng, Yuan; et al.
Abstract: Transparent electrodes that form seamless contact and enable optical interrogation at the electrode–brain interface are potentially of high significance for neuroscience studies. Silk hydrogels can offer an ideal platform for transparent neural interfaces owing to their superior biocompatibility. However, conventional silk hydrogels are too weak and have difficulties integrating with highly conductive and stretchable electronics. Here, a transparent and stretchable hydrogel electrode based on poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) and PEGylated silk protein is reported. PEGylated silk protein with poly(ethylene glycol) diglycidyl ether (PEGDE) improves the Young's modulus to 1.51–10.73 MPa and the stretchability to ≈400% from conventional silk hydrogels (<10 kPa). The PEGylated silk also helps form a robust interface with PEDOT:PSS thin film, making the hydrogel electrode synergistically incorporate superior stretchability (≈260%), stable electrical performance (≈4 months), and a low sheet resistance (≈160 ± 56 Ω sq −1 ). Finally, the electrode facilitates efficient electrical recording, and stimulation with unobstructed optical interrogation and rat‐brain imaging are demonstrated. The highly transparent and stretchable hydrogel electrode offers a practical tool for neuroscience and paves the way for a harmonized tissue–electrode interface. Abstract : Transparent, stretchable neural electrodes based on silk hydrogel are demonstrated. PEGylation improves the stretchability and water stability of the silk hydrogel, and contributes to a robust interface with poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate. The hydrogel electrode allows a highly stretchable electrical coupling with tissues, which facilitates simultaneous electrical and optical interrogation of neural circuits. This work offers an efficient hydrogel tool for neuroscience and clinical applications.